ICCREM 2017. proceedings of the International Conference on Construction and Real Estate Management 2017, November 10-12 2017, Guangzhou, China - Wang, Yaowu; Pang, Yongshi; Shen, Qiping; Zhu, Yimin (College teacher) (American Society of Civil Engineers, 2017)
This collection contains 45 peer-reviewed papers on industry regulation and sustainable development. Topics include: performance analysis in sustainable development; regulations and efficiency in construction; and collaboration models in green development.
Keywords: Construction industry -- Environmental aspects -- Congresses.; Sustainable buildings -- Design and construction -- Congresses.; Construction industry -- Environmental aspects -- China -- Congresses.; Sustainable buildings -- China -- Design and construction -- Congresses.; Sustainable engineering -- Congresses.; elektronické knihy; electronic books